2022
DOI: 10.1002/2688-8319.12184
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic distance controls plant growth during early restoration of a semi‐arid riparian forest

Abstract: 1. Little attention has been paid to phylogenetic diversity during restoration initiatives. Because plant phylogenetic distance can be a surrogate for functional diversity, its consideration could foster the restoration of degraded areas.2. This study investigates the influence of species richness and phylogenetic relatedness during early restoration of a riparian forest located between the Atlantic Forest and semi-arid ecosystems in NE Brazil. The restoration experiment was established along a perennial strea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Hence, assessing changes in resource availability in our experimental plots warrants further investigation. Not sharing closely related common ancestors, species in HDP communities tend to have different morphological and functional attributes that allow them to make differential use of resources (Kraft et al 2007 ; Cavender-Bares et al 2009 ), leading to increased survival (Chaves et al 2021 ), plant growth, and positive plant–plant interactions (Tucker et al 2018 ; Teixeira et al 2022 ). For example, some studies have observed that nurse species facilitate growth for distantly related species than for closely related ones (i.e., with high phylogenetic distance; Valiente-Banuet and Verdú, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, assessing changes in resource availability in our experimental plots warrants further investigation. Not sharing closely related common ancestors, species in HDP communities tend to have different morphological and functional attributes that allow them to make differential use of resources (Kraft et al 2007 ; Cavender-Bares et al 2009 ), leading to increased survival (Chaves et al 2021 ), plant growth, and positive plant–plant interactions (Tucker et al 2018 ; Teixeira et al 2022 ). For example, some studies have observed that nurse species facilitate growth for distantly related species than for closely related ones (i.e., with high phylogenetic distance; Valiente-Banuet and Verdú, 2007 ).…”
Section: Discussionmentioning
confidence: 99%